Seasonal pattern of preterm birth in the Netherlands: A population-based retrospective cohort study - Nadine D. de Klerk; Ivar R. de Vries; Phebe B. Q. Berben; Annemarie F. Fransen; Myrthe van der Ven; Rik Vullings; M. Beatrijs van der Hout-van der Jagt; S. Guid Oei; Judith O. E. H. van Laar (PLoS ONE, 2025)
Background Prior research has demonstrated the impact of environmental influences, including seasonal patterns, as determinants of preterm birth, although relationships vary. This study aims to determine whether there is an association between month of conception and preterm birth or gestational age at birth in the Netherlands. Methods This was a population-based retrospective cohort study with data collected between 2015–2019. Data originated from the national perinatal registry in The Netherlands, of which 828,574 deliveries were included. Relationships between month of conception and birth with gestational age at delivery were investigated. Furthermore, trends in the preterm birth rate among women diagnosed with imminent preterm birth were investigated. Additionally, the relationship between outdoor temperature, humidity, hours of sunlight with preterm birth was examined to investigate their possible role in preterm birth’s pathophysiology. Results The distribution of gestational age at birth showed significant variation over the months of conception when all births, spontaneous onset of delivery, or iatrogenic onset of delivery were considered (all p < 0.001). Preterm and term births were more common for conception between January and June, whereas birth >41 weeks of gestation was most common for conception between July and December. Seasonal or monthly variation in preterm birth rate among women diagnosed with imminent preterm birth was not significant (p = 0.103). Higher humidity was associated with higher preterm birth rates (HR = 1.003, 95% CI: 1.001–1.005), whereas higher outdoor temperature (HR = 0.998, 95% CI: 0.996–1.000) and more sunlight exposure (HR = 0.994, 95% CI: 0.995–0.998) were associated with lower preterm birth rates. Conclusions Pregnancies conceived in January through June are associated with a higher risk of preterm birth. These outcomes demonstrate a seasonal pattern and identify environmental risk factors for preterm birth. These patterns might be a result of fluctuations in melatonin levels, governed by variation in the hours of daily sunshine over the year in the Netherlands.